Factors influencing the intention of choosing an electric vehicle in Pengkalan Chepa, Kelantan - Muhammad Wafi Ahmad Nazri; Syazana Husna Abu Samah; Gan Wei Li; Nurshamira Abdul Samad (2023)
A type of transportation that runs on electricity is known as an electric vehicle (EVs). EVs use an electric motor that is powered by electricity from batteries or a fuel cell, as opposed to conventional vehicles that use a gasoline (petrol) or diesel-powered engine. To meet various driving requirements, there are three different types of EVs. They come in three varieties: fuel cell, plug-in hybrid, and all-electric. But one of the serious barriers to EVs may be the cost of purchasing one. EVs are generally more expensive than conventional internal combustion engine vehicles, despite the fact that their costs are beginning to decline. The main objective of this study is to see the intention of choosing EVs in Pengkalan Chepa, Kelantan with related factors which are environmental concern, psychological benefits, price range, perception of economic benefits, and infrastructure readiness. This study will distribute questionnaires to respondents among the Pengkalan Chepa, Kelantan residents in order to collect data using a quantitative research approach. Quantitative research method was used and 140 respondents were evaluated. Questionnaire were distributed to collect the primary data as a survey with online questionnaire and personally to get the information needed for this study. All the data collected was analyzed by using IBM SPSS Version 26 software based on descriptive statistics, reliability analysis, Pearson correlation analysis, and multiple regression analysis. As for the result, most of the independent variables have a significant relationship with the dependent variable. Through this study, it will understand the factor that factor influencing the intention of choosing an electric vehicle.